Knowledge Management Framework Implementation In Government To Increase Organization Performance - Marsha Hapsari, Swasthi (Pusat Publikasi Nusantara, 2023)
The Jak preneur Program is one of Dinas PPUMKM's most successful MSME empowerment and development initiatives in Jakarta. MSMEs are critical to the global economy, contributing to job creation, innovation, and economic growth. However, they frequently face challenges in effectively harnessing and utilizing their knowledge assets to drive competitiveness, particularly for the DKI Jakarta Provincial Government (Pemprov DKI Jakarta). This study investigates the implications of knowledge management in a government organization's Jak preneur program under the supervision of Dinas PPUKM (Provincial Government Department of Industry, Trade, Small and Medium-sized Enterprises). Furthermore, the study's findings will help MSMEs overcome the lack of knowledge-based growth barriers. This thesis investigates the concept of knowledge management (KM) in the context of public government organizations. The goal of this study is to provide a comprehensive analysis of Knowledge Management practices in government organizations, examining current approaches, challenges, and potential strategies and frameworks for improvement. The study employs a qualitative approach that includes in-depth interviews and focuses on group discussions (FGD) with multiple perspectives from MSME owners, managers, mentors, and facilitators in order to identify knowledge gaps, which will be classified into four categories: people, processes, technology, and governance. Each stakeholder is expected to participate in the knowledge management process, accelerating the organization's goal of raising the standard of its MSMEs. The study's findings can help policymakers, MSME practitioners, and researchers design and implement effective knowledge management initiatives. The proposed system is intended to be used to clarify the management of Dinas PPUMKM (Provincial Government Department of Industry, Trade, Small and Medium-sized Enterprises), including not only roles and responsibilities but also how the knowledge management system can improve the company's day-to-day performance.